2017
DOI: 10.1158/0008-5472.can-16-0725
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Redirected to a Minor Histocompatibility Antigen Instruct Intratumoral TNFα Expression and Empower Adoptive Cell Therapy for Solid Tumors

Abstract: Donor-derived allogeneic T cells evoke potent graft versus tumor (GVT) effects likely due to the simultaneous recognition of tumor-specific and host-restricted minor histocompatibility (H) antigens. Here we investigated whether such effects could be reproduced in autologous settings by TCR gene-engineered lymphocytes. We report that T cells redirected either to a broadly expressed Y-encoded minor H antigen or to a tumor-associated antigen, although poorly effective if individually transferred, when simultaneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Finally, we also found that low‐dose Iso1/Au/IL12 could enhance the efficacy to adoptive T cell therapy in mice with autochthonous prostate cancer. In these mice, T cells redirected to the tumor by a TCR gene transfer approach fail to evoke tumor rejection, unless combined with additional tumor‐targeting strategies . Our results show that adoptive T‐cell therapy in combination with low‐dose Iso1/Au/IL12 promotes tumor regression in the majority of mice.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Finally, we also found that low‐dose Iso1/Au/IL12 could enhance the efficacy to adoptive T cell therapy in mice with autochthonous prostate cancer. In these mice, T cells redirected to the tumor by a TCR gene transfer approach fail to evoke tumor rejection, unless combined with additional tumor‐targeting strategies . Our results show that adoptive T‐cell therapy in combination with low‐dose Iso1/Au/IL12 promotes tumor regression in the majority of mice.…”
Section: Discussionmentioning
confidence: 84%
“…Although more recent studies showed that toxicity could be limited by engineering T cells with inducible IL12 constructs,15f we reasoned that the controlled delivery of an extremely low‐dose, well‐defined, of IL12 might prove a safer approach. To test the hypothesis that low‐dose Iso1/Au/IL12 might be of help in the context of adoptive T‐cell therapy (ACT) we used the transgenic prostate adenocarcinoma mouse model (TRAMP), with autochthonous prostate cancer development, and T cells redirected by TCR gene transfer to the tumor‐associated large T antigen . Notably, previous studies have shown that in this model tumor‐redirected T cells lack significant therapeutic activity, unless used in combination of vessel‐targeted TNF or minor histocompatibility redirected T cells .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations